New developments in catheter ablation for patients with congenital heart disease. (2nd January 2021) - Le Bloa, Mathieu; Abadir, Sylvia; Nair, Krishnakumar; Mondésert, Blandine; Khairy, Paul
ABSTRACT: Introduction : There are numerous challenges to catheter ablation in patients with congenital heart disease (CHD), including access to cardiac chambers, distorted anatomies, displaced conduction systems, multiple and/or complex arrhythmia substrates, and excessively thickened walls, or interposed material. Areas covered : Herein, we review recent developments in catheter ablation strategies for patients with CHD that are helpful in addressing these challenges. Expert opinion : Remote magnetic navigation overcomes many challenges associated with vascular obstructions, chamber access, and catheter contact. Patients with CHD may benefit from a range of ablation catheter technologies, including irrigated-tip and contact-force radiofrequency ablation and focal and balloon cryoablation. High-density mapping, along with advances in multipolar catheters and interpolation algorithms, is contributing to new mechanistic insights into complex arrhythmias. Ripple mapping allows the activation wave front to be tracked visually without prior assignment of local activation times or window of interest, and without interpolations of unmapped regions. There is growing interest in measuring conduction velocities to identify arrhythmogenic substrates. Noninvasive mapping with a multielectrode-embedded vest allows prolonged bedside monitoring, which is of particular interest in those with non-sustained or multiple arrhythmias. Further studies are required to assess the role of radiofrequency needle catheters and stereotactic radiotherapy in patients with CHD.